2021
DOI: 10.1007/s10896-021-00290-5
|View full text |Cite
|
Sign up to set email alerts
|

“The Stay at Home Order is Causing Things to Get Heated Up”: Family Conflict Dynamics During COVID-19 From The Perspectives of Youth Calling a National Child Abuse Hotline

Abstract: The purpose of this study was to identify changes in family conflict and abuse dynamics during COVID-19 stay-at-home orders from the perspectives of youth calling a national child abuse hotline. We analyzed text and chat transcripts from Childhelp’s National Child Abuse Hotline from May–June 2020 that were flagged as coming from a child with a COVID-19-related concern (N = 105). Thematic analysis was used to identify COVID-19 related influences of family conflict as well as how COVID-19 constraints influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Required social isolation guidelines may have weakened the social networks that buffer parents' harsh parenting practices (Lee, Ward, Lee et al, 2021). Factors such as household and parenting stress (Connell & Strambler, 2021;Rodriguez et al, 2021b), unemployment (Lawson et al 2020Rodriguez et al, 2021b), exposure to other forms of family violence such as IPV (Humphreys et al, 2020), and social isolation (Bullinger et al, 2020;Lee, Ward, Lee et al, 2021;Sinko et al, 2021) each contributed to elevated child abuse risk during the pandemic. Indeed, studies demonstrated high levels of harsh parenting during the pandemic (Connell & Strambler, 2021;Sari et al, 2021), with elevated abuse risk and psychological aggression observed even after controlling for pre-pandemic levels (Rodriguez et al, 2021b).…”
Section: Applying Socio-emotional Information Processing Theory To Ex...mentioning
confidence: 99%
“…Required social isolation guidelines may have weakened the social networks that buffer parents' harsh parenting practices (Lee, Ward, Lee et al, 2021). Factors such as household and parenting stress (Connell & Strambler, 2021;Rodriguez et al, 2021b), unemployment (Lawson et al 2020Rodriguez et al, 2021b), exposure to other forms of family violence such as IPV (Humphreys et al, 2020), and social isolation (Bullinger et al, 2020;Lee, Ward, Lee et al, 2021;Sinko et al, 2021) each contributed to elevated child abuse risk during the pandemic. Indeed, studies demonstrated high levels of harsh parenting during the pandemic (Connell & Strambler, 2021;Sari et al, 2021), with elevated abuse risk and psychological aggression observed even after controlling for pre-pandemic levels (Rodriguez et al, 2021b).…”
Section: Applying Socio-emotional Information Processing Theory To Ex...mentioning
confidence: 99%
“…They were thus at risk for overload, exhaustion and depression (Calvano et al 2021 ; McLaren et al 2020 ; Taylor et al 2021 ). Spending more time in confined spaces also resulted in more frequent family conflicts and sometimes led to physical and sexual abuse or maltreatment (Rodriguez et al 2021 ; Sinko et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study that recruited survivors from intimate partner violence and sexual assault-focused agencies reported that survivors experienced increased difficulty staying safe and accessing resources, as well as an increase in stress from economic instability ( Wood et al, 2021 ). Additionally, in analyzing chat and transcript data from the National Child Abuse Hotline, researchers identified real-time effects of the pandemic on children, including heightened violence in the home and limited access to social support or safe spaces while social distancing measures were in place ( Sinko et al, 2021 ). This study offered unique insights based on data from an anonymous chat-based hotline, a uniquely accessible resource during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon the work of Sinko et al (2021) , we aimed to understand the pandemic-related experiences and concerns of sexual violence survivors. We analyzed open-ended data collected via staff who interacted with users of the National Sexual Assault Online Hotline.…”
Section: Introductionmentioning
confidence: 99%